Effects of dietary fiber on human health - Yang He; Bixiang Wang; Liankui Wen; Fengzhong Wang; Hansong Yu; Dongxia Chen; Xin Su; Chi Zhang (Food Science and Human Wellness)
Dietary fiber (DF) is believed to provide important health benefits and it has become a research hotspot. DF exists in most natural foods, including fruits (16.74%–91.24%), vegetables (6.53%–85.19%), grains (9.76%–69.20%) and so on. DF has different physicochemical properties such as water holding capacity (WHC) (2.01–25.03 g/g), water swelling capacity (WSC) (0.95–23.90 mL/g), oil holding capacity (OHC) (0.65–29.00 g/g), glucose adsorption capacity (GAC) (0.17–4.65 mmol/g), cholesterol adsorption capacity (CAC) (0.03–37.10 mg/g) and viscosity, which make it exhibits different physiological functions such as reducing the risk of obesity, diabetes, cancer, and intestinal diseases. On the basis of consulting related databases, the physicochemical properties of DF and its derived physiological functions are reviewed. It is found that DF has effect on the prevention and treatment of obesity due to good WHC, WSC, OHC and CAC. Good GAC can relieve the symptoms of diabetes. The physicochemical properties of WHC and WSC can reduce the risk of cancer. The WHC, WSC and viscosity are beneficial to intestinal health.